INISIATIF Culture Health Index: Mengukur Tingkat Kesehatan Budaya Organisasi BPJS Kesehatan - Syarifuddin Syarifuddin; Afrizayanti; andi afdal (Jurnal Jaminan Kesehatan Nasional, 2022)
Background: Organizational culture is one of the key HR management elements in BPJS Kesehatan. Optimal management of organizational culture is expected to be able to make a significant contribution to achieving organizational targets, starting from careful planning, effective and efficient program execution, and measuring the effectiveness of cultural programs as an objective evaluation mechanism. To improve the management of organizational culture that is more optimal in the future, an objective evaluation is very important to do. Purpose: This study aims to obtain an overview of the level of organizational culture health index in BPJS Kesehatan. Methods: This study uses a descriptive quantitative approach. Data collection was carried out by filling out the Organization Culture Health Index (OCHI) survey by all BPJS Kesehatan employees as respondents (the participation rate in filling out the survey was 96.79% of the population) and focus group discussions (FGD) to obtain the required qualitative information. Results and Discussion: Based on the measurement results, the level of organizational culture health in BPJS Kesehatan is generally in the "Healthy Enough" category with a total index value of 72.6%. The implementation index of the 4 main values ​​is as follows: excellent service (71.3%), integrity (69.0%), innovative (67.6%), and collaboration (63.7%) and has been integrated into 5 awareness areas organization, namely: sustainability, relationship, growth, common goals, and meaning purpose area. The level of positive energy felt by employees at work is in the "High" category with an index value of 95.2%. This is because organizational culture as one of the important elements of HR management, has succeeded in forming a fun and meaningful work atmosphere to create positive energy felt by employees. Conclusions and Recommendations: BPJS Kesehatan is considered quite successful in internalizing organizational culture. INISIATIF as the main value system can be understood and become a shared belief for employees. However, in the context of optimizing the management of organizational culture, BPJS Kesehatan is expected to be able to enrich the latest literature reviews, perform benchmarking, especially to other organizations that have succeeded in forming a healthy organizational culture, and make various breakthroughs and innovations in managing organizational culture. Thus, it is hoped that the organizational culture at BPJS Kesehatan can reach the "Healthy" category and be able to form an organizational image that is recognized by all parties involved in the JKN ecosystem